Transformation of the form and content of teaching foreigners in the context of innovative development of education - Селіверстова, Л. І. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2016)
The article deals with the problem of modern methods of teaching Ukrainian as a foreign language, namely, a transformation of the form and content of teaching Ukrainian to foreign students in the light of current innovative development of education and availability of technical means of teaching. The author describes methods that allow promoting acquisition of learning material. The main attention is focused on creation of new forms of training (transnational, distance, short-term, highly specialized, socio-cultural) and on resources which provide them, as well as on the problem of choosing a language of training (Ukrainian, Russian, and English). The author investigates the decrease in necessity to use capital letters, which is related to the practicality of modern gadgets. Communicative competence is regarded as the main factor of training foreigners that affects the content and form of teaching Ukrainian at universities ofUkraine. Speech is regarded as the basis of everyday and classroom communication, as a result of creative intellectual activity manifested in a variety of genres and forms and as a part of the communicative competence of foreign students. Modern technical equipment allows using different teaching material and helps to activate various mechanisms of memory, create conditions for communicative competence cultivation, i.e. the foreigner’s awareness of the motive, the purpose of communication, special features of the addressee, speech subject, and the main idea. The author’s attention has been paid to various types of communication involved in the process of teaching foreigners (formal / informal, personal / public, collective / mass, emotive / emotional). The author has analyzed a number of educational techniques and features, such as a flexible individualized mode and a rate of studying, self-planning of the learning process by students, diagnostic monitoring of the learning process and its adjustment in accordance with the individual characteristics of the students performing the training program.The author compares traditional and innovative methods of teaching that increase the general effectiveness of knowledge acquisition.